2016
DOI: 10.1039/c5ob02080h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting anti-apoptotic Bcl2 proteins with scyllatoxin-based BH3 domain mimetics

Abstract: BH3 domain mimetics based on the small protein scyllatoxin (ScTx) were designed to target the anti-apoptotic protein Bcl2 in vitro. Intrinsically disordered ScTx variants were found to bind Bcl2 with nanomolar affinity, indicating that an induced fit binding mechanism is required for favorable BH3 : Bcl2 interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 31 publications
(51 reference statements)
2
32
0
Order By: Relevance
“…Extensive structure-activity relationship studies carried out on disulfide-rich sequences derived from animal venoms have led to approved drugs (e.g., ziconotide for chronic pain, hirudin for anticoagulation) as well as a number of compounds in clinical development. [2] Expanding beyond their natural functions, disulfide-rich scaffolds have also been engineered as de novo ligands for protein surfaces, [3] with sequences derived from rational design, [4] computational, [5] as well as directed evolution approaches. [6] …”
Section: Introductionmentioning
confidence: 99%
“…Extensive structure-activity relationship studies carried out on disulfide-rich sequences derived from animal venoms have led to approved drugs (e.g., ziconotide for chronic pain, hirudin for anticoagulation) as well as a number of compounds in clinical development. [2] Expanding beyond their natural functions, disulfide-rich scaffolds have also been engineered as de novo ligands for protein surfaces, [3] with sequences derived from rational design, [4] computational, [5] as well as directed evolution approaches. [6] …”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found that ScTx-based BH3 domain mimetics containing three disulfide linkages did not bind Bcl-2 in vitro [24]. However, removing all three disulfides rescued the ability for ScTx-based BH3 domain mimetics to target Bcl-2 proteins with submicromolar affinity, indicating that an induced-fit binding mechanism is required for favorable BH3:Bcl2 interactions [24,28]. These findings prompted us to explore how discrete structural elements, such as individual disulfide linkages, affected the folding and activity of ScTx-based BH3 domain mimetics.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, ScTx contains three disulfides that contribute to its folded structure; each of these disulfides can, in theory, be added or removed depending on the structural requirements of the molecular interaction being investigated. Surprisingly, we found that ScTx-based BH3 domain mimetics containing three disulfide linkages did not bind Bcl-2 in vitro [24]. However, removing all three disulfides rescued the ability for ScTx-based BH3 domain mimetics to target Bcl-2 proteins with submicromolar affinity, indicating that an induced-fit binding mechanism is required for favorable BH3:Bcl2 interactions [24,28].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…These data would suggest that the helical content of the ligand is not sufficient to induce a cellular response: Indeed, 10 and 13 possess higher helical content than 5, but contrarily to the latter, they had no effect on the cells. This might be due to an unfavorable interaction pattern displayed by the cyclopeptide (Figure S7) or to a loss of conformational dynamics: In this regard, it has been recently reported that the highly rigid three-disulfidebonded scyllatoxin was not suitable for protein grafting and Bcl-2 protein targeting; however, its reduced form was, suggesting the importance of induced fit mechanisms in binding to the Bcl-2 protein [82].…”
Section: Discussionmentioning
confidence: 99%